Two new parasitic copepods of the family Sphyriidae (Copepoda: Siphonostomatoida) from Australian elasmobranchs - Geoff A. Boxshall; Diane P. Barton; Amy Kirke; Xiaocheng Zhu; Grant Johnson (Systematic Parasitology, 2022)
Two new species of the genus Tripaphylus Richiardi in Anonymous, 1878 (family Sphyriidae) are described from elasmobranch hosts caught as bycatch within the Demersal and Timor Reef Fisheries which operate in the Northern Territory exclusive economic zone. Tripaphylus squidwardi n. sp. was collected from Carcharhinus coatesi Whitley and had a prevalence of 11.6%. Tripaphylus dippenaarae n. sp. was collected from Rhizoprionodon acutus (Rüppell) and had a prevalence of 28.2%. The new species are distinguished from existing congeneric species by the body proportions and shape of the adult female and by the arrangement of lobes on the ventral surface of the cephalothorax.

A new parasitic copepod (Copepoda; Cyclopoida; Chondracanthidae) from two pomacentrid fishes caught on the Great Barrier Reef, Queensland, Australia - Geoff A. Boxshall (Systematic Parasitology, 2022)
A new species of the copepod genus Pseudacanthocanthopsis Yamaguti & Yamasu, 1959 (family Chondracanthidae) is described based on material of both sexes collected from two pomacentrid host fishes caught off Lizard Island, Queensland. The type host is Neopomacentrus azysron (Bleeker) and the additional host is N. cyanomos (Bleeker). The new species is distinguishable from all congeners by the form of the antennule of the female, which is dorso-ventrally flattened and extends out anteriorly to the front of the cephalothorax margin.

A new copepod (Siphonostomatoida: Lernanthropidae) parasitic on a Red Sea immigrant dragonet (Actinopterygii: Callionymidae), with a review of records of parasitic copepods from dragonets - Hoda H. El-Rashidy; Geoff A. Boxshall (Systematic Parasitology, 2012)

The discovery of Caligus temnodontis Brian, 1924 (Copepoda: Caligidae) from the bluefish Pomatomus saltatrix (Linnaeus) in the eastern Mediterranean Sea - Argun A. Özak; Hoda H. El-Rashidy; İbrahim Demirkale; Geoff A. Boxshall (Systematic Parasitology, 2010)

Parasitic copepods on immigrant and native clupeid fishes caught in Egyptian coastal waters off Alexandria - Hoda El-Rashidy; Geoff A. Boxshall (Systematic Parasitology, 2010)

A revision of the family Dissonidae Kurtz, 1924 (Copepoda: Siphonostomatoida) - Geoff A. Boxshall; Ching-Long Lin; Ju-Shey Ho; Susumu Ohtsuka; B. A. Venmathi Maran; Jean-Lou Justine (Systematic Parasitology, 2008)

Global diversity of copepods (Crustacea: Copepoda) in freshwater - Geoff A. Boxshall; Danielle Defaye (Hydrobiologia, 2008)

Three new species of Enterocola van Beneden, 1860 (Crustacea: Copepoda: Cyclopoida) from ascidian hosts - Andrey Marchenkov; Geoff A. Boxshall (Systematic Parasitology, 2005)

The notodelphyid Genus Doroixys Kerschner, 1879 (Crustacea: Copepoda: Cyclopoida), with the Description of a New Species from the Russian Far East - Andrey Marchenkov; Geoff A. Boxshall (Systematic Parasitology, 2004)

Phylogeny within the Chondracanthidae (Poecilostomatoida, Copepoda) - Pia Østergaard; Geoff A. Boxshall; Donald L. J. Quicke (Zoologica Scripta, 2003)
The existing systematics of the Chondracanthidae is based predominantly on female characters and divides them into two subfamilies: Chondracanthinae and Lernentominae. Phylogenetic analyses using maximum parsimony were performed using 186 male and female characters. Different trees were generated when male and female characters were analysed separately. Differential weighting showed that the female characters were dominant but not to a great extent and subsequent analyses were run with both partitions combined. Different trees were generated depending on the character setting (unordered, ordered and irreversible‐up). Interestingly, a basal backbone comprising the same nine ingroup taxa was present in all of the trees, although the sequence of those taxa could differ. Constraining the two subfamilies to be monophyletic caused the tree length to be increased and the Templeton and Kishino–Hasegawa tests showed the constrained tree to be significantly different from the unconstrained. The two subfamilies are considered invalid and Lernentominae Oakley, 1927 is formally synonymized with Chondracanthinae Milne Edwards, 1840. The validity of the Pharodidae was tested similarly. Pharodes tortugensis , representing the family Pharodidae, was always recovered nested deep within Chondracanthidae. The Pharodidae Illg, 1948 is therefore synonymized with the Chondracanthidae Milne Edwards, 1840.

A new notodelphyid copepod, Paranotodelphys illgi n. sp. (Copepoda: Cyclopoida), parasitic in the ascidian Corynascidia herdmani Ritter in the North Pacific - Andrey Marchenkov; Geoff A. Boxshall (Systematic Parasitology, 2003)

The Buproridae Thorell, 1859, a family of ascidicolous copepods (Copepoda: Cyclopoida) - Andrey Marchenkov; Geoff A. Boxshall (Systematic Parasitology, 2002)

New species and new records of Ergasilus Nordmann (Copepoda: Ergasilidae) from the gills of grey mullet (Mugilidae) - Hoda H. El-Rashidy; Geoff A. Boxshall (Systematic Parasitology, 2002)

Gauchergasilus, a new genus for Ergasilus euripedesi Montú, 1980, an abundant parasitic copepod from the Patos Lagoon in southern Brazil - Monica A. Montú; Geoff A. Boxshall (Systematic Parasitology, 2002)

A new species of Taeniastrotos Cressey (Copepoda: Poecilostomatoida) from southern Brazil - Monica A. Montú; Geoff A. Boxshall (Systematic Parasitology, 1997)